The impact of cash flows on the financial performance of companies - An analytical study on the Saudi telecommunications sector - - Sabri, Shaimaa Yusuf; Abdulrahman, Najla Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the Net Cash Flows, from operational, investment and financing activities, impact on financial performance in terms of profitability through return on assets and return on property rights in the Saudi telecommunications sector. The study sample included (3) companies within Saudi telecommunications companies, and covered a 10-year period of time, from 2009 to 2018. The financial and statistical analysis is used to examine the study’s hypotheses and questions, through the reports of the companies listed in the Capital Market and published on the Tadawul site as well as private companies’ websites. To test the validity of the hypotheses and to get to the relevant statistical significances, the multiple regression coefficients and the SPSS program were used. The study found a statistically significant impact of Net Cash Flows of the Net Cash Flows of operational activities, Net Cash Flows of investment activities, and Net Cash Flows of finance activities, at the level of (= 0.05), on financial performance (return on asset index - return on property rights index). The researcher suggested a set of recommendations, the most important of which is the need to pay attention to the cash flows list since its provide financial information free of misinformation as it is real data and depend on the monetary base, and carrying out the study of cash flows in its three divisions (operational, financing and investment) on other economic sectors to illustrate the relationship between cash flows and the financial performance of companies.